2014
DOI: 10.1310/hpj4908-752
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast

Abstract: Each month, subscribers to The Formulary Monograph Service receive 5 to 6 well-documented monographs on drugs that are newly released or are in late phase 3 trials. The monographs are targeted to Pharmacy & Therapeutics Committees. Subscribers also receive monthly 1-page summary monographs on agents that are useful for agendas and pharmacy/nursing in-services. A comprehensive target drug utilization evaluation/medication use evaluation (DUE/MUE) is also provided each month. With a subscription, the monographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Apremilast showed obvious effects on innate immunity and cellular immunity, especially the release of inflammatory mediators with a wide therapeutic index in ferret lung neutrophilia model, when compared with its gastrointestinal effects (Schafer et al, 2014 ). After great efforts, apremilast (brand name Otezla, Figure 3B ) was approved in 2014 for treatment in adults who suffered from active PsA and moderate-to-severe plaque psoriasis (Cada et al, 2014 ; Varada et al, 2014 ; Chiricozzi et al, 2016 ). A pharmacokinetic study found that apremilast is absorbed well from the gut with independence of food intake and is mainly metabolized by CYP450 3A4, with minor contributions from CYP1A2 and CYP2A6, to about 23 metabolites clarified in plasma, urine, and feces (Bianchi et al, 2016 ).…”
Section: Approved Pde4 Inhibitors For the Treatment Of Inflammatory Dmentioning
confidence: 99%
See 3 more Smart Citations
“…Apremilast showed obvious effects on innate immunity and cellular immunity, especially the release of inflammatory mediators with a wide therapeutic index in ferret lung neutrophilia model, when compared with its gastrointestinal effects (Schafer et al, 2014 ). After great efforts, apremilast (brand name Otezla, Figure 3B ) was approved in 2014 for treatment in adults who suffered from active PsA and moderate-to-severe plaque psoriasis (Cada et al, 2014 ; Varada et al, 2014 ; Chiricozzi et al, 2016 ). A pharmacokinetic study found that apremilast is absorbed well from the gut with independence of food intake and is mainly metabolized by CYP450 3A4, with minor contributions from CYP1A2 and CYP2A6, to about 23 metabolites clarified in plasma, urine, and feces (Bianchi et al, 2016 ).…”
Section: Approved Pde4 Inhibitors For the Treatment Of Inflammatory Dmentioning
confidence: 99%
“…A pharmacokinetic study found that apremilast is absorbed well from the gut with independence of food intake and is mainly metabolized by CYP450 3A4, with minor contributions from CYP1A2 and CYP2A6, to about 23 metabolites clarified in plasma, urine, and feces (Bianchi et al, 2016 ). Apremilast exposure is unexpectedly reduced when coadministered with CYP450 inducers, such as rifampin, phenobarbital, carbamazepine, and phenytoin, which may result in the loss of therapeutic efficacy (Cada et al, 2014 ).…”
Section: Approved Pde4 Inhibitors For the Treatment Of Inflammatory Dmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro CYP metabolism of apremilast is primarily mediated by CYP3A4. Thus, the use of apremilast in conjunction with CYP450 enzyme inducers such as rifampin, phenobarbital, carbamazepine and phenytoin is not recommended [1][2][3][4]. The pharmacokinetic profile of apremilast is not affected by moderate or severe hepatic impairment.…”
Section: Clinical Pharmacologymentioning
confidence: 99%